2015
DOI: 10.5430/jct.v4n2p96
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Dimensions of the Physical Educators’ Judgments about Inclusion Instrument: Brazilian-Version

Abstract: Background/Objective: The available information pertaining to the attitudes of Brazilian physical education teachers about teaching students with disabilities is limited in the extant literature base. Rationally, however, scholars argue that determining, analyzing, and theorizing about the attitudes of physical education teachers is important in the preparation and professional development of these teachers. It is therefore important to extend the research base using valid and reliable measures regarding teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Oh and colleagues' study (2010) revealed that teacher related variables found to affect attitudes toward teaching students with disabilities including perceived competence, experience teaching students with disabilities, and preparation in special education or adapted physical education. Also, other studies showed that teachers' competence (Conatser et al, 2002), experience (Hodge et al, 2015), attitude (Trip & Rizzo, 2006) were variables related to teachers' intentions as well as other attributes. However, little study has been done yet to link Korean physical education teachers' attributes with teaching behavior.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Oh and colleagues' study (2010) revealed that teacher related variables found to affect attitudes toward teaching students with disabilities including perceived competence, experience teaching students with disabilities, and preparation in special education or adapted physical education. Also, other studies showed that teachers' competence (Conatser et al, 2002), experience (Hodge et al, 2015), attitude (Trip & Rizzo, 2006) were variables related to teachers' intentions as well as other attributes. However, little study has been done yet to link Korean physical education teachers' attributes with teaching behavior.…”
mentioning
confidence: 93%
“…Currently, approximately 6.4 million students in public schools are receiving special education services and this amounts is about 13% of the national school-aged population (U.S. Department of Education, 2011). As a result of the inclusion movement in the United States, more of these students are now being educated in physical education classes (Block & Obrunsnikova, 2007;Hodge et al, 2015;Lieberman & Houston-Wilson, 2013).…”
mentioning
confidence: 99%